Mapping Public Participation in EIA in Indonesia: Recommendations for an Ideal Concept - Annisa Fianni Sisma; I Gusti Ayu Ketut Rachmi Handayani; Lego Karjoko; Ravi Danendra (Faculty of Law, Sriwijaya University, Indonesia, 2025)
A quality EIA document is directly proportional to the level of public participation that influences the preparation process. However, the EIA level of public participation in Indonesia is still very low , even reduced after being amended by Law No. 32/2009 in conjunction with Law No. 6/2023, which shows that public participation has not been prioritised. Several factors influence this, including the reduction of EIA participation through Law No. 6/2023, as well as the involvement of parties and forms that are not in line with the needs of the community. This research aims to identify the level of public participation in preparing EIA in Indonesia and present ideal concepts and recommendations regarding these three aspects. This legal research uses a statutory and conceptual approach with primary and secondary legal materials (Law No. 32/2009 in Lieu of Law No. 6/2023, Government Regulation No. 22/2021 and relevant scientific works). The level of public participation in the EIA preparation process in Law No. 6/2023 tends to be lower than before because the community cannot influence the final decision; affected parties are limited; forms of participation are limited to providing suggestions, opinions and responses; and the public participation in government institutions is eliminated. Therefore, the ideal concept uses a mapping that includes the parties involved, the form, and the purpose of participation with three rationales, namely normative, substantive, and instrumental, which are briefly related to the community role, the quality of environmental decisions, and the basis of legitimacy. The government needs to develop ideal regulations for public participation in preparation for EIA based on this mapping so that the preparation of EIA is participative, transparent, equitable, and informed.